Estudo da expressão e da compreensão na criança com base em provas de linguagem oral e escrita - Pinto, Maria da Graça Lisboa Castro (1986)
The starting point of this study is the basis of analysis supplied by A. Girolami-Boulinier and the methodology used by that author is a similar study already undertaken in the French language. The critical analysis from the points of view of expression, vocabulary and comprehension was based upon stories told orally by 60 pre-primary children and 60 children of the first year of schools in the Oporto area. These results in the Portuguese language can provide some references which will allow the study of the language of a given child and the linguistic localization of certain disorder when a pathological case is being treated.